A meta-analysis of observational studies on anticholinergic burden and fracture risk: evaluation of conventional burden scales - Yukari Ogawa; Toshinori Hirai; Kiyoshi Mihara (BMC, 2021)
Abstract Background Anticholinergic burden potentially increases the risk of fracture. Although there are various anticholinergic burden scales, little is known about the inter-scale compatibility regarding the relationship of anticholinergic burden with fracture risk. We performed meta-analysis to examine the association of fracture risk with anticholinergic burden measured using various scales. Methods Primary literature was retrieved from PubMed (1966 to March, 2021), the Cochrane Library (1974 to March, 2021), Scopus (1970 to March, 2021), and Ichushi-web (1983 to March, 2021). Cohort and case-control studies that evaluated the association between any fracture and anticholinergic drugs were included. Additionally, we included studies in which patients were administered anticholinergic drugs included on the anticholinergic risk scale (ARS), anticholinergic cognitive burden (ACB), anticholinergic drug scale, or drug burden index-anticholinergic component. Random effects models were used to calculate pooled relative risk (RR) and 95% confidence interval (CI) due to heterogeneity among the studies. Publication bias was examined by funnel plots and the Begg's test. Results A total of 49 datasets from 10 studies were included in the meta-analysis. Six of the 10 studies included only patients aged over 65 years, who accounted for 93% of the total study population (453,186/487,247). Meta-analysis indicated a positive relationship between use of anticholinergic drugs and fracture risk, regardless of the anticholinergic burden scale used. However, the relationship between anticholinergic burden and fracture risk varied depending on the scale used. Fracture risk increased linearly with increasing anticholinergic burden measured using ARS. ARS 1 point was associated with 28% increase in fracture risk, ARS 1-2 point(s) with 39%, ARS 2 points with 54%, ARS 3 points with 66%, and ARS ≥ 4 points with 77%. On the other hand, ACB 1 point and ACB 2 points were associated with similar fracture risk (pooled RR [95% CI]: overall; 1.28 [1.18-1.39], 1 point; 1.12 [1.06-1.18], 2 points; 1.15 [1.08-1.23]). Conclusions This result suggests that the relationship between anticholinergic drug burden and fracture risk may differ depending on the anticholinergic burden scale used.